2010
DOI: 10.1080/19359701003622875
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Clients: Identifying and Minimizing Barriers to Mental Health Treatment

Abstract: This study examined mental healthcare use and barriers to mental healthcare utilization in a sample of 130 transgender volunteers. Roughly a third of participants sought treatment for mental health issues including depression, anxiety, and relationship problems. Sixty-eight participants (52% of sample) showed evidence of psychological distress but had not received mental health services in the past year. Results point to potential barriers to seeking mental health services. Specifically, cost of treatment, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 17 publications
5
131
0
1
Order By: Relevance
“…As a result, trans people have reported needing to educate mental health professionals about trans issues (del Pozo de Bolger, et al, 2014;McNeil, et al, 2012). Negative experiences such as those outlined above are concerning, given research suggests that previous negative experiences with mental health services, or knowing someone who has had a negative experience, are barriers to accessing services (Shipherd, et al, 2010). This issue of trans people's negative experiences with mental health professionals is significant given the fact that mental healthcare professionals may be the first people with whom some trans people discuss their gender (Hunt, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, trans people have reported needing to educate mental health professionals about trans issues (del Pozo de Bolger, et al, 2014;McNeil, et al, 2012). Negative experiences such as those outlined above are concerning, given research suggests that previous negative experiences with mental health services, or knowing someone who has had a negative experience, are barriers to accessing services (Shipherd, et al, 2010). This issue of trans people's negative experiences with mental health professionals is significant given the fact that mental healthcare professionals may be the first people with whom some trans people discuss their gender (Hunt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Yet previous research suggests that many trans people have negative experiences with mental health care providers (e.g., del Pozo de Bolger, Jones, Dunstan, & Lykins, 2014;Ellis, Bailey, & MacNeil, 2015; McNeil, Bailey, Ellis, Morton, & Regan, 2012;Riggs, Coleman, & Due, 2014). Specifically, trans people have reported that some professionals may lack experience or skills for working with trans clients (Ellis, et al, 2015;Sperber, Landers, & Lawrence, 2005), and may lack knowledge and sensitivity about trans-specific issues (Ellis, et al, 2015;Hunt, 2014;Jones, del Pozo de Bolger, Dune, Lykins, & Hawkins, 2015;Pitts, Couch, Croy, Mitchell, & Mulcare, 2009;Shipherd, Green, & Abramovitz, 2010). As a result, trans people have reported needing to educate mental health professionals about trans issues (del Pozo de Bolger, et al, 2014;McNeil, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The modules included case studies, such that each theoretical and practical aspect of the training was paired with real-life cases of LGBTcompetent therapy examples (e.g., from our Romanian clinical research). Otherwise, the training content was based on previous research and clinical scholarship regarding LGBT mental health, 27,52,[56][57][58][59][60][61] direct clinical practice experience in the United States, and our provision of similar trainings, workshops, and seminars in the United States.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…This module presented counseling models that affirm and support LGBT individuals to reduce psychological distress arising from stigma and nonaffirmative healthcare. 52,[58][59][60]62,63 Providers were trained in helping LGBT clients find supportive communities and relationships. The module reviewed selfaffirming communication skills, building safe networks to overcome isolation and depression; safe disclosure of sexual orientation (when and to whom, including in healthcare contexts); and navigation of hostile contexts.…”
Section: Modulementioning
confidence: 99%
“…al, 2010). These findings encourage clinicians to address and examine how gender role adherence impacts a client's experience with their diagnosis (Rosenfield, & Mouzon, 2013;Doherty & Kartalova O'Doherty, 2010;Shipherd et. al, 2010).…”
Section: Dedicationmentioning
confidence: 99%